Efectos del control de cambio en el intercambio comercial con Colombia. Consecuencias del retiro de Venezuela de la Comunidad Andina - Mayora Guaita, Humberto José (Revista Venezolana de Análisis de Coyuntura, 2013)
Esta investigación tiene como objetivos analizar las causas que propiciaron un escenario donde se observa el comercio binacional con impulso, máximas y caídas abruptas, pero que de un amanera u otra manera se necesitan para su complemento. La metodología empleada consiste en la investigación documental. Finalmente estos acontecimientos están relacionados con los rigores del Régimen de Control Cambiario empleado en Venezuela llamado CADIVI que inciden en el precio de los productos que a diario se registran en diversas transacciones realizadas por empresarios y comercializadores del lado colombiano y registraron para finales de 2011 un intercambio de 2.193 millones de dólares. Abstract Effects of exchage control in the commercial exchange with Colombia. Consequences of the retirement of Venezuela of the andean community The main purpose of this paper is to analyze the reasons why, in the last four years, the binational trade between Colombia and Venezuela has experimented a steady growth, a positive boost, high economical peaks and, at the same time, abrupt falling in terms of figures of trade exchange. It is considered that a possible cause of this situation is linked to the rigorous Control of Monetary Exchange employed by the National Monetary Exchange Control Bureau called CADIVI in Venezuela. This state of affair has had an effect on the prices of the commercial products. Such effect has been regularly recorded by Colombian entrepreneurs and traders through their various regular business transactions. For instance, by the end of 2011, it was registered an exchange of 2.193 dollars. In order to meet the objectives stated in this research it was used a documentary methodology.